Hypo-cortisolism, early onset obesity and liver disease in a child with homozygous proopiomelanocortin mutation - Joshi, Rajesh; Malagi, Krishna (International Journal of Contemporary Pediatrics, 2021)
The peptide derivatives of proopiomelanocortin molecule are involved in energy homeostasis, regulation of food intake, skin pigmentation and augment biliary flow. Homozygous mutation in POMC gene, which is inherited in an autosomal recessive pattern, is associated with hyperphagia leading to early onset obesity, hypoglycaemia and neonatal cholestasis due to cortisol deficiency and red hair pigmentation as a result of alpha MSH deficiency. We report a child having multiple episodes of hypoglycemia with this disorder who presented like liver disease. Our case report highlights the importance of early suspicion of this rare condition and confirmation with genetic analysis.